Effect of interrupting free healthcare for children: Drawing lessons at the critical moment of national scale-up in Burkina Faso. (July 2017) - Druetz, Thomas; Bicaba, Abel; Some, Telesphore; Kouanda, Seni; Ly, Antarou; Haddad, Slim
Abstract: With solid evidence that free healthcare increases the utilization of health services, Burkina Faso recently exempted all children under five and pregnant women from direct payment at health facilities. However, there is little insight into the capacity to maintain the gains attributable to free healthcare under routine conditions of implementation at the national scale. In particular, the repercussions of its interruption are unknown. The objective is to assess the effects of a sequence of natural interventions including the introduction, interruption and reintroduction of free healthcare on health-seeking practices and utilization of healthcare facilities by children under five. This is an embedded mixed methods study conducted in Kaya district, Burkina Faso. The quantitative component is based on a reversal longitudinal design. Pooled interrupted time-series analysis was performed to assess changes in the monthly number of visits from January 2005 to March 2015. Qualitative data were collected through in-depth interviews with health personnel and mothers to better understand the quantitative results. The results show that visits to health centres dropped immediately and significantly when free healthcare was interrupted (−146, CI95% [-255; −37]). They increased again when free healthcare was reintroduced (+89, CI95% [-11; 187]). Both urban and rural centres were affected. Self-medication and visits to traditional healers were reported more frequently during the withdrawal of free healthcare, and tensions between the population and health personnel increased. Implementation problems other than insufficient funding limited the coverage or intensity of free healthcare. While removing user fees could potentially improve mothers and children's health in Burkina Faso, this study shows that demand for healthcare remains highly sensitive to price changes. Gains in utilization attributable to free healthcare may vanish rapidly if user fees are reintroduced. It is essential to support an effective and sustainable implementation of this ambitious initiative. Highlights: Demand for healthcare remains very elastic to price changes in Burkina Faso. Visits to health centres immediately drop when free healthcare is interrupted. Long-term funding is one amongst several implementation challenges. Sustainability and high fidelity are both required for a successful scaling-up. Gains in utilization attributable to free care may vanish rapidly with user fees' reintroduction.